Floral Phenology and Pollination Ecology of Punica granatum L. in Kathmandu, Nepal - Adhikari, Subodh; Adhikari, Mahesh Kumar (Nepal Journal of Science and Technology, 2011)
The phenological and ecological study on Punica granatum L., a cultivated and wild species found in outer Himalayan ranges and warm inner valleys (alt. 700 - 2700m), was carried out during April and May of 2006 and 2007 in Kathmandu Valley. The study covered blooming time, size of flower, its correlation and interaction with the visitors and pollinators. The prime pollinator was Apis cerena along with A. mellifera. Normal range of the length of a full blooming flower (mature flower) was 4.1 to 4.7 cm (in bagged flower) and 3.8 to 4.9 cm (in open flower). The fruiting rate was higher in case of the open flowers than the bagged one. Visitor's/pollinator's flower visit rate (visits/time) was found higher (most effective) in morning with sunny weather (766 times out of 1365). Similarly, the least effective time was dawn and dusk with cloudy and rainy weather (2 times each out of 1365). Key words: floral phenology; visitors/pollinators DOI: 10.3126/njst.v11i0.4133 Nepal Journal of Science and Technology 11 (2010) 115-124